2015
DOI: 10.1093/mmy/myv106
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofHistoplasma capsulatumfrom clinical specimens by cycling probe-based real-time PCR and nested real-time PCR

Abstract: We developed new cycling probe-based real-time PCR and nested real-time PCR assays for the detection of Histoplasma capsulatum that were designed to detect the gene encoding N-acetylated α-linked acidic dipeptidase (NAALADase), which we previously identified as an H. capsulatum antigen reacting with sera from patients with histoplasmosis. Both assays specifically detected the DNAs of all H. capsulatum strains but not those of other fungi or human DNA. The limited of detection (LOD) of the real-time PCR assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Laboratory-developed PCR assays using a variety of molecular targets have been developed (Table 4). Compared to culture and a criterion-based or clinical diagnosis of histoplasmosis, the sensitivity of molecular assays in published studies has ranged between 67 and 100% (30-35) and 33 and 87% (36,37), respectively. A fluorescence in situ hybridization (FISH) technique that successfully detects H. capsulatum rRNA in blood cultures may circumvent the need for colony growth to obtain a definitive and timely diagnosis (35).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Laboratory-developed PCR assays using a variety of molecular targets have been developed (Table 4). Compared to culture and a criterion-based or clinical diagnosis of histoplasmosis, the sensitivity of molecular assays in published studies has ranged between 67 and 100% (30-35) and 33 and 87% (36,37), respectively. A fluorescence in situ hybridization (FISH) technique that successfully detects H. capsulatum rRNA in blood cultures may circumvent the need for colony growth to obtain a definitive and timely diagnosis (35).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Unfortunately, commercial kits to detect Histoplasma antigens based on enzyme immunoassay are still not available in China. PCR, nested PCR and real-time PCR using Histoplasma specific primers were reported to distinguish cultured Histoplasma from other pathogenic fungi [14]. There are few reports on the detection of capsular Histoplasma by high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR was performed on all samples from the 12 patients to screen for Influenza A virus (in-house developed), Coronavirus (in-house developed), Black creek canal virus (in-house developed), Andes virus (inhouse developed), Guanarito virus (in-house developed), Sabia virus (inhouse developed), Nipah virus (in-house developed), Flavivirus (in-house developed), Leptospira [12,13], and Histoplasma [14,15], according to the cited publications or in-house protocols.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The results of this work led the authors to conclude that multicopy targets were the best option when designing an assay as they provide and increase in sensitivity without decreasing specificity; real time PCR proved to be more advantageous than conventional PCR. In contrast, one study limited to a small number of samples from a single laboratory showed a better sensitivity of nested PCR assays as compared to designs based on cycling-probe real-time PCR (Muraosa et al, 2016). Such differences highlight the need of collaborative networks to assess the diagnostic yield of different molecular assay designs for the diagnosis of histoplasmosis, particularly in areas of low prevalence.…”
Section: Molecular Alternatives To Diagnose Histoplasmosismentioning
confidence: 95%